Studi kasus: identifikasi ektoparsit pada ikan Nila (Oreochromis niloticus) yang dipelihara pada keramba jaring apung - Rahman, M. Gazali; Handayani, Leni (Universitas Sam Ratulangi, 2022)
The purpose of this study was to determine the type of ectoparasites and to determine the level of prevalence, intensity, and dominance in tilapia. This research was conducted using an experimental method. Sampling was carried out in floating net cages in Pematang Limau Village, 10 samples of tilapia were taken for each sampling and then examined in the laboratory. During fish sampling, water samples were also taken to analyze the ammonia and dissolved oxygen content. Sample organs including scales, fins, mucus and gills were examined using scraping and biopsy methods. The results showed that there were 3 types of ectoparasites that attack tilapia based on the organs they attack, namely Argulus sp., Trichodina sp. and Oodinium sp. The prevalence of parasites that occur in tilapia shows that fish are very often infected, where the average prevalence of Argulus sp. 35%, Trichodina sp. 45% and Oodinium sp. 55%. The intensity of the parasite that attacked tilapia during the study was in the mild category, namely the intensity value ranged from 1.79 to 18.33 ind/fish while the type of parasite that dominated was Oodinium sp.